Implementasi Metode Talaqqi Pada Pembelajaran Al-Qur’an - Setiawan, Agung; Hartati, Zainap; Luthfi, Saiful (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
Learning the Qur’an is a central pillar of Islamic education, which not only focuses on memorization but also emphasizes tajwid accuracy, comprehension, and spiritual formation. This study aims to analyze the implementation of the talaqqi method in Qur’anic learning at Darul Amin Islamic Boarding School in. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving teachers and students. The findings reveal that the talaqqi method is applied intensively through direct teacher–student interaction, conducted individually and in small groups with a rotation reading system. Regular evaluations are carried out through memorization submissions and observation of students’ attitudes. The results indicate that the talaqqi method significantly strengthens tajwid accuracy, improves memorization quality, and fosters discipline, focus, and spiritual awareness in students. Supporting factors include competent teachers, student motivation, a conducive pesantren environment, and consistent learning routines, while the main challenges are limited time, large student numbers, and minimal technology integration. This study highlights the relevance of the talaqqi method as a traditional Islamic pedagogical approach that remains effective in preserving Qur’anic authenticity and character building